2019
DOI: 10.1029/2018wr023289
|View full text |Cite
|
Sign up to set email alerts
|

Downscaling Vertical GPS Observations to Derive Watershed‐Scale Hydrologic Loading in the Northern Rockies

Abstract: GPS time series of vertical displacement include the elastic response of the Earth to a combination of regional and local loading signals arising from hydrologic mass transfer. The regional loading, controlled by seasonal, synoptic precipitation patterns, dominates the displacement of individual stations and is highly correlated among stations with separation distances from 10 to 300 km. The local loading, controlled by small‐scale precipitation and storage variability, has much shorter correlation lengths of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 51 publications
0
42
0
Order By: Relevance
“…The potential of using ground‐based GPS vertical displacements to represent TWS interannual variations was investigated via the removal of the mean seasonal cycle (i.e., the multiyear average of each month) of vertical displacement embedded within the time series derived from GPS, GRACE, and Catchment. Again, the network‐wide mean of seasonally adjusted vertical displacement time series following Knappe et al (2019) was calculated for GPS, GRACE, and Catchment as shown in Figure 7. A positive, residual vertical displacement (i.e., after removing the mean seasonal cycle) represents a larger than multiyear averaged displacement for that particular month, which indicates less hydrologic loading than during expected climatology.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential of using ground‐based GPS vertical displacements to represent TWS interannual variations was investigated via the removal of the mean seasonal cycle (i.e., the multiyear average of each month) of vertical displacement embedded within the time series derived from GPS, GRACE, and Catchment. Again, the network‐wide mean of seasonally adjusted vertical displacement time series following Knappe et al (2019) was calculated for GPS, GRACE, and Catchment as shown in Figure 7. A positive, residual vertical displacement (i.e., after removing the mean seasonal cycle) represents a larger than multiyear averaged displacement for that particular month, which indicates less hydrologic loading than during expected climatology.…”
Section: Resultsmentioning
confidence: 99%
“…(3) SNOTEL SWE measures mass loading resting on a snow pillow, and any mass moving off the sensor (e.g., via snow melt or wind redistribution) generally remains in the surrounding region and, by construct, is measured in the integrated TWS signal but not measured in the local SNOTEL SWE signal (Knappe et al, 2019); and (4) the separation distance between GPS and SNOTEL stations is not the only factor that influences the correlation; e.g., other factors such as elevation difference between the stations should also be considered. Errors in the collection and processing of GPS and SNOTEL measurements can also introduce additional discrepancies.…”
Section: Surface Deformation and Hydrologic Loadingsmentioning
confidence: 99%
“…GPS vertical displacements reflect deflection of the crust excited by changes in hydrologic load; SNOTEL SWE measures effective snow depth at specific locations. In the Northern Rockies snowpack is the dominant hydrologic input (Serreze et al, 1999), and the two measures are correlated (Knappe et al, 2019).…”
Section: Time Series Analysis and Statisticsmentioning
confidence: 99%
“…Alternatively, other studies have linked seasonal variations in seismicity to increases in pore pressure with some delay from peak hydrologic load or precipitation (Christiansen et al, 2005;Johnson et al, 2020;Saar & Manga, 2003;Wolf et al, 1997). Invoking this mechanism, seismic productivity increases will occur after a lag from peak runoff and infiltration, which occurs in late spring to early summer (e.g., Knappe et al, 2019) (Figure 3). As this would result in a minimum cross correlation (or maximum anticorrelation) with SWE rate and a maximum cross correlation with GPS rate at a ∼6-month shift, this interpretation is also supported PERRY AND BENDICK (Figure 4).…”
Section: Perry and Bendickmentioning
confidence: 99%
“…This method also provides a new perspective on achieving a relatively high spatio-temporal resolution of TWS depending on the spatial density and distribution of the continuous GPS network [ 19 ]. In addition, GPS is a ground-based observation technology that should be more sensitive to variations in the overall regional hydrological compartments, including groundwater, nearby reservoirs [ 20 ], snow [ 21 ], and runoffs [ 22 ]. This implies that a ground-based GPS-inferred TWS should reflect the regional characteristics of TWS distribution more realistically than inferred from space-borne GRACE [ 23 ].…”
Section: Introductionmentioning
confidence: 99%